The influence of competence on organizational performance in government institutions: A case study - Sarfilianty Anggiani; Tri Agung Widayat; Feti Fatonah (International Journal Labs, 2024)
This study aims to determine the influence of personnel competence on organizational performance in government agencies. The data are collected and analyzed systematically. The results show that, in the Ministry of Transportation, higher competencies among state civil servants (ASNs) lead to improved employee performance and contribute positively to organizational outcomes. The research contributes to understanding the relationship between employee competence and organizational performance within government agencies, especially in the Department of Transportation. Moreover, longitudinal studies could be conducted to assess the long-term effects of personnel development programs on organizational performances over time. This study provides valuable insights for improving efficiency and effectiveness in public sector operations. The study also highlights the importance of investing in training and development programs to enhance employee competencies, ultimately leading to better service delivery and achievement of organizational goals.